Efforts to Improve Learning Outcomes in Mathematics and Indonesian Language by Using the NHT (Numberd Heads Together) Type Cooperative Learning Model on the Theme of Healthy and Clean Living in Class II Semester 2 SD Negeri Balak, Cawas District, Klaten Regency in the 2021/2022 School Year - Widayati, Rohmi (Universitas Sebelas Maret, 2022)
The purpose of writing this Classroom Action Research is: to find out whether the NHT (Numberd Heads Together) Type Cooperative Learning Model can improve student learning achievement in mathematics and Indonesian Language. The data collection was obtained through the observation, interviews, and questionnaires for quantitative data analysis, as well as using post-tests for quantitative analysis. The variable of this research is improving student learning achievement in Mathematics and Indonesian Language subjects. The theme of Healthy and Clean Living Using the NHT (Numberd Heads Together) Type Cooperative Learning Model for class II of SD Negeri Balak, Cawas District, Klaten Regency in semester 2 of the 2021/2022 academic year. The sample was taken using all class II students, which happened to be 14 students. From the results of data analysis, it can be obtained that the Qualitative Value is in the range of 70% and above and the average value of learning outcomes in cycle I is 56.42, while in cycle II the average value is 66.42, cycle III is 78.57. Also the completeness of student learning in the cycle In the first cycle there were 4 students (28.57%) out of 14 children, in the second cycle there were 8 children (57.14%) out of 14 students and in the third cycle it rose to 14 children (100%) and had reached 70% or more.